P2P network identity authentication mechanism based on trusted alliance - Yingying CHEN; Feng ZHANG; Wenbao JIANG; Xu ZHOU (网络与信息安全学报)
In order to effectively solve the problems of CA's cross certification and single point of failure in traditional PKI system,a new identity authentication mechanism was proposed.Firstly,this mechanism built the basic architecture based on blockchain,and built the trusted alliance by dynamically generating trusted nodes.Secondly,the whole network unified unique identity was proposed and used a new data structure,named SRT,to store.Finally,all nodes in the network could mutual authentication through the double layer consensus mechanism.Experiments show that this mechanism can meet the query and management of massive user identity information,and ensure the efficiency and security in the identity authentication process.